Universidade, Extensão e Sociedade : um estudo das ações na área da saúde na UFSCar (2004/2014) - Barros, Regina Lourenço de (Universidade Federal de São Carlos, 2016)
The university extension is a communication channel between the university and society. By extension, the university can keep in contact with reality and participate in the solution of social problems, contributing to local and national development. Development means not only economic growth but includes changes in society aimed at improving the quality of life. In this sense, health has substantial involvement in the concept of development. Universities - notably the UFSCar – have been directing much of their extension actions to the health field. Within this context, the aim of this study was to analyze the university extension activities of UFSCar in the health area, notedly the activities developed in the Department of Medicine (DMed) to evaluate its contribution to the development of the city of São Carlos. A survey was conducted to identify the extension activities related to health between 2004 and 2014, recorded in ProExWeb information channel of the Pro-Rectory of UFSCar extension. Then the Dmed activities were analyzed to check the different types of actions undertaken and its potential to contribute to the improvement of health quality of the residents of São Carlos. As a result of this research it was observed that UFSCar conducted a very large amount of healthrelated activities in this period. The number of these activities came steadily growing over time in the various departments directly linked to the training of health professionals, with special emphasis on the Department of Medicine (DMed). From this research we can infer that these activities contributed to improvement in education, promotion, prevention, recovery and rehabilitation in the health area of São Carlos region.
Keywords: Extensão universitária; Saúde; Desenvolvimento; Ensino Superior; Development; Higher education; Health; OUTROS